ADVANCE system testing: Estimating the incidence of adverse events following pertussis vaccination in healthcare databases with incomplete exposure data. (22nd December 2020) - Dodd, Caitlin; de Ridder, Maria; Weibel, Daniel; Mahaux, Olivia; Haguinet, Francois; de Smedt, Tom; de Lusignan, Simon; McGee, Chris; Duarte-Salles, Talita; Emborg, Hanne-Dorthe; Huerta-Alvarez, Consuelo; Martín-Merino, Elisa; et al.
Highlights: Incidence rates of events following vaccination can be derived when exposure data is missing. Incidence rate ratios from databases with complete exposure data can be used to derive IRs. Type of database and event reporting methods determines bias for derived IRs. Background incidence can be used to derive risk period incidence if the risk period is short. Abstract: The Accelerated Development of VAccine beNefit-risk Collaboration in Europe (ADVANCE) is a public–private collaboration aiming to develop and test a system for rapid vaccine benefit-risk monitoring using existing European healthcare databases. Incidence rate (IR) estimates of vaccination-associated adverse events that are needed to model vaccination risks can be calculated from existing healthcare databases when vaccination (exposure) data are available. We assessed different methods to derive IRs in risk periods following vaccination when exposure data are missing in one database, using estimated IRs and IRRs from other databases for febrile seizures, fever and persistent crying. IRs were estimated for children aged 0–5 years in outcome-specific risk and non-risk periods following the first dose of acellular pertussis (aP) vaccination in four primary care databases and one hospital database. We compared derived and observed IRs in each database using three methods: 1) multiplication of non-risk period IR for database i by IR ratio (IRR) obtained from meta -analysis of IRRs estimated using the self-controlled case-series method, from databases other than i ; 2) same method as 1, but multiplying with background IR; and 3) meta -analyses of observed IRs from databases other than i . IRs for febrile seizures were lower in primary care databases than the hospital database. The derived IR for febrile seizures using data from primary care databases was lower than that observed in the hospital database, and using data from the hospital database gave a higher derived IR than that observed in the primary care database. For fever and persistent crying the opposite was observed. We demonstrated that missing IRs for a post-vaccination period can be derived but that the type of database and the method of event data capture can have an impact on potential bias. We recommend IRs are derived using data from similar database types (hospital or primary care) with caution as even this can give heterogeneous results.